2022
DOI: 10.2196/30454
|View full text |Cite
|
Sign up to set email alerts
|

A Quality Improvement Emergency Department Surge Management Platform (SurgeCon): Protocol for a Stepped Wedge Cluster Randomized Trial

Abstract: Background Despite many efforts, long wait times and overcrowding in emergency departments (EDs) have remained a significant health service issue in Canada. For several years, Canada has had one of the longest wait times among the Organisation for Economic Co-operation and Development countries. From a patient’s perspective, this challenge has been described as “patients wait in pain or discomfort for hours before being seen at EDs.” To overcome the challenge of increased wait times, we developed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The main concern among commentators was that the healthcare system has reached its breaking point. Doctors and nurses are overworked and have to work longer hours than any other department in the hospital (Mariathas et al, 2022) because the surplus of patients in the ED waiting room leads to a backlog of patients. This backlog leads to extremely long wait times in the ED, and some patients' symptoms can worsen immensely, resulting in the patient's overall health decreasing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main concern among commentators was that the healthcare system has reached its breaking point. Doctors and nurses are overworked and have to work longer hours than any other department in the hospital (Mariathas et al, 2022) because the surplus of patients in the ED waiting room leads to a backlog of patients. This backlog leads to extremely long wait times in the ED, and some patients' symptoms can worsen immensely, resulting in the patient's overall health decreasing.…”
Section: Discussionmentioning
confidence: 99%
“…SurgeCon aims to improve ED wait times and department efficiency and was piloted in an ED in Carbonear, Newfoundland and Labrador. During the piloting of SurgeCon, the results indicated that despite the increase in ED patient volume, the number of patients had an overall decrease (Mariathas et al, 2022). The pilot study allowed SurgeCon to allot to other EDs and assess how this platform's incorporation affects EDs.…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40] At sites across Newfoundland and Labrador researchers are using SurgeCon, 41 a home-grown quality improvement initiative using ED and hospital data to apply real-time protocols to manage surges in ED visits before they occur, reducing ED length of stay. 42,43 At Niagara Health -St. Catherine's Site (Ontario) patient flow simulation exercises were used to help an interdisciplinary team decide where to offload ambulance arrivals and transfer patients needing a bed. 44 In Toronto the Hospital for Sick Children and St. Michael's Hospital have both used forms of machine learning and artificial intelligence to understand when surges will happen in their EDs.…”
Section: Surge Management and Predictionmentioning
confidence: 99%
“…The typical duration of a visit to an ED is around 3.5 hours, which poses a risk to patients since prolonged waiting times in EDs have been associated with suboptimal patient outcomes (Magid et al, 2009;Bernstein et al, 2008;Pines & Hollander, 2008;Fee et al, 2007;Sprivulis et al, 2006;Richardson, 2006;Derlet & Richards, 2000), and to the increased likelihood of adverse events (Guttmann, 2011). To address this issue, SurgeCon, a quality improvement program, was devised to address the lack of integration, sustainability and logistical issues which negatively impact wait times in EDs (Anaraki et al, 2022, Mariathas et al, 2022Patey, et al, 2019). SurgeCon delivers its quality improvement program through a department level management platform that encompasses three key elements: the installation and con guration of a tailored eHealth system, organizational restructuring, and the establishment of a patient-centric environment.…”
Section: Introductionmentioning
confidence: 99%